Strategies and Proficiency in Language Learning Among College Students in the New Normal (Conference on English Language Teaching, 2023)
Learning of English as second and even foreign language has been stressed out in all degrees of education. Consequently, academics and researchers have concentrated on depicting the outwardly discernible actions of linguists came after by making an effort to identify and name strategic actions, then connect them to language proficiency. This study was an exploration of college students’ strategies and proficiency in language learning. Language proficiency of the students was significantly lower than anticipated, partially confirming the teacher's assessment of low proficiency levels as evidence of students' general inadequacy for studying English at national curriculum-required levels. This descriptive research involved 260 respondents who were randomly selected to respond to the adopted SILL (Strategy Inventory for Language Learning) questionnaire. Mean and Pearson r were used as statistical tools. The data revealed that the students practice high language learning strategies, specifically more on metacognitive and affective strategies. Meanwhile, a moderate level of language proficiency was found out. Statistically, there was no statistical evidence showing significant relationship between language learning strategies and language proficiency. The findings of the study suggest important implications for classroom instruction and learning content design. Students, especially those with low proficiency levels, can be assisted to improve their competence in English through strategy instruction.